Fetomaternal hemorrhage - case report - Jakub Gruszka; Anna Zwierzyńska; Magdalena Dolecka-Ślusarczyk; Olga Adamczyk-Gruszka (Kazimierz Wielki University, 2022)
Maternal fetal leakage (FMH) is a well-known cause of fetal anemia. We define it as the transition of the fetal erythrocytes into the maternal circulation. Its severity is determined by measuring the level of fetal hemoglobin in the mother's blood using the Kleinhauer-Betke test or the cytometric method (FCM). The paper presents a case of a newborn with massive maternal-fetal leakage. The maternal blood Kleinhauer test result was greater than 5% of the fetal blood cells, and the initial neonatal hemoglobin level was 3.5 g / dl. Correct treatment of fetal anemia is presented. The additional studies performed allowed for the exclusion of other causes as a result of the extremely severe condition of the newborn after delivery. Early diagnosis of fetal-maternal leak and its treatment through execution.